Halo(natrono)archaea isolated from hypersaline lakes utilize cellulose and chitin as growth substrates - Sorokin, Dimitry Y. (Frontiers in Microbiology, 2015)
Until recently, extremely halophilic euryarchaeota were considered mostly as aerobic heterotrophs utilizing simple organic compounds as growth substrates. Almost nothing is known on the ability of these prokaryotes to utilize complex polysaccharides as cellulose, xylan and chitin. Although few haloarchaeal cellulases and chitinases were recently characterized, the analysis of currently available haloarchaeal genomes deciphered numerous genes encoding glycosidases (GHs) of various families including endoglucanases and chitinases. However, all these haloarchaea were isolated and cultivated on simple substrates and their ability to grow on polysaccharides in situ or in vitro is unknown. This study examines several halo(natrono)archaeal strains from geographically distant hypersaline lakes for the ability to grow on insoluble polymers as a sole growth substrate in salt-saturated mineral media. Some of them belonged to known taxa, while other represented novel phylogenetic lineages within the class Halobacteria. All isolates produced extracellular extremely salt tolerant cellulases or chitinases, either cell-free or cell-bound. Obtained results demonstrate a presence of diverse population of haloarchaeal cellulo/chitinotrophs in hypersaline habitats indicating that euryarchaea participate in aerobic mineralization of recalcitrant organic polymers in salt-saturated environments.